Proposed Energy Based Method for Light Receiver Localization in Underground Mining - Soto-Gomez, J; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2016)
Light source localization is one of the most functional area in light signal processing. Various methods are used for light localization. Most of these methods are based on image signal processing on 2-D recorded image of environment but they need more devices for image recording. The aim of this paper, is localization of a photodetector or light receiver. These light receivers are used in connection with light sources, because as seen, light is not emitted from these photodetectors. Then, actually, the image processing based methods are useless in this application. The method in this paper is based on energy calculation in different frequency range based on received light from different light sources. Firstly, the effect of different light sources is separated by smart filtering. Then, the place of light receiver is estimated by energy calculation on specific frequency range and finding the intersection of spheres due to each light source. The benefit of the proposed method is using 1-D signal and needless of any specific device and in all of environment conditions. This proposed method can be implemented in real time due to low computational complexity. Also, this method has less complexity in compare with image processing based methods. Moreover, the accuracy of the proposed method is equal or sometimes better than the image processing based methods. The proposed method in this paper has been evaluated in different environmental conditions and the results shows a good accuracy. Also, this method can be used in underground mining applications. © 2016 IEEE.